2012
DOI: 10.3315/jdcr.2012.1099
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5% imiquimod cream in a patient with classic Kaposi sarcoma

Abstract: Background: The classic Kaposi sarcoma is most common in the Mediterranean population over 50 years of age and presents with reddish-brown papules and nodules particularly on the lower limbs. Treatment depends on the clinical presentation and extension of lesions. Imiquimod is as an immune response modifier with antiangiogenic activity. Main observations:We present a 74-year-old man with classic Kaposi sarcoma who had multiple, small, violaceous papules and nodules on the trunk and extremities with a history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Some case reports showed successful treatment of single classic KS in HIV-negative patients with 3 times per week application under occlusion for 12 weeks. 9,17 Some needed daily application for 4 months in 1 HIV patient, 12 and nightly under occlusion for multiple classic KS in an HIV-negative patient that required 1 year of application before clearance. 15 The treatment period may be the other significant point to increase the efficacy of imiquimod, which was applied for only 12 weeks in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case reports showed successful treatment of single classic KS in HIV-negative patients with 3 times per week application under occlusion for 12 weeks. 9,17 Some needed daily application for 4 months in 1 HIV patient, 12 and nightly under occlusion for multiple classic KS in an HIV-negative patient that required 1 year of application before clearance. 15 The treatment period may be the other significant point to increase the efficacy of imiquimod, which was applied for only 12 weeks in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to be highly effective against KS in some case reports in the literature. [9][10][11][12][13][14][15][16][17] There is only 1 trial wherein imiquimod in KS was investigated for its antitumour activity, showing antitumour activity in 8 of 17 patients. 2 Our study is designed to evaluate the effect of imiquimod, which is distinguished from other local treatment methods by its at-home application, on classic KS lesions compared with cryotherapy, which is one of the most-used treatment methods for KS in our department.…”
Section: Introductionmentioning
confidence: 99%
“…87,88 Case reports have shown that imiquimod cream can be safe and effective in some patients with classic or transplant-associated Kaposi sarcoma. [89][90][91][92][93][94] In a single-center, open-label, phase I/II trial, 17 HIV-negative patients with Kaposi sarcoma received imiquimod 5% cream 3 times per week for 24 weeks. 95 The response rate was 47%.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…Imiquimod acts by activating cytokines that have an antagonistic role in angiogenesis, pro-angiogenic factor down-regulation and induction of apoptosis in endothelial cells. [ 39 ] Goiriz et al [ 40 ] reported a successful treatment outcome using 5% imiquimod cream in an 87-year-old man with widespread nodules of classical KS on both his lower limbs. Another patient with successful outcome following the usage of 5% imiquimod cream in a thrice weekly schedule for localized KS under occlusion for 8 h for a period of 3 months has been reported by Bernardini et al [ 41 ]…”
Section: Uses Of Imiquimod In Cutaneous Premalignant and Malignant Comentioning
confidence: 99%